The Healthier the Tastier? USA–India Comparison Studies on Consumer Perception of a Nutritious Agricultural Product at Different Food Processing Levels - Dubé, Laurette; Fatemi, Hajar; Lu, Ji; Hertzer, Cristian (Frontiers in Public Health, 2016)
Present research compares food beliefs associated with a naturally nutritious agricultural commodity (namely pulses) in Western and Eastern cultures (namely US and India). Specifically, this paper focuses on the perception of healthiness and tastefulness of the food and their relationship. Two studies tested the effect of processing level, cultural differences and branding strategies. In contrast to the well-established inverse relationship between healthiness and tastefulness beliefs observed in the West with industrial food products, the results of both studies revealed a positive association between health and tastefulness for pulses in both West and East. Study1 shows that this positive association is stronger with lower processing, suggesting the role of naturalness as bridge between health and taste. Focusing on cultural differences, results show that while both West and East hold positive association of health and taste for pulses, this association is stronger for East. However, the role of processing level is significantly stronger in West. Study2 looks at branding strategies for pulse products with different processing levels in West and East. Results confirm the findings of study1 on positive association of taste and healthiness and cross cultural differences. Moreover, study2 shows that cultural differences between West and East changes the effectiveness of branding strategies on food related belief and attitude towards food. For American consumers a future oriented branding is associated with an enhanced positive healthiness-taste association, whereas a brand image emphasizing tradition leads to increased perception of the taste of product but not necessarily on the healthiness. Current paper has theoretical and practical implications in public policy, health and marketing.